High-bonding-strength composite coating on surface of nuclear zirconium alloy and preparation method of high-bonding-strength composite coating

By using laser melting technology on the surface of the alloy to prepare the MO/Hastelloy C2000 double -layer coating structure, the problem of insufficient intensity of existing coating at high temperature conditions has achieved the high binding strength and length of the coating and the alloy alloys. Effect protection effect.

CN119352012APending Publication Date: 2025-01-24SHANGHAI JIAOTONG UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411488929.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The metal Cr coating on the surface of existing zirconium alloy shells is insufficient in combination under high temperature conditions, which is prone to Cr-Zr diffusion, causing coating dissolution failure, and under high temperature oxidation conditions, bulging and cracks fall off from the zirconium alloy, which cannot be provided. Long-term protection.

Method used

Laser cladding technology is used to prepare a Mo/Hastelloy C2000 double-layer coating structure on the surface of zirconium alloy. Mo serves as an intermediate layer to block the interdiffusion of elements and improve the metallurgical bonding strength of the coating and zirconium alloy.

Benefits of technology

It significantly improves the intensity of the binding intensity of the coating and the alloy, enhances the corrosion resistance and long -term protection capabilities of the coating under high temperature oxidation conditions, and ensure that the coating still maintains a good combination under stretching strain conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119352012A_ABST
    Figure CN119352012A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of laser cladding surface modification, and particularly discloses a high-bonding-strength composite coating on the surface of a nuclear zirconium alloy and a preparation method of the high-bonding-strength composite coating, and a Mo intermediate layer and a Hastelloy C2000 coating outer layer are prepared on the surface of the zirconium alloy in sequence by adopting a laser cladding process. The specific method comprises the following steps: drying metal powder with the particle size of 53-105 microns for more than 4 hours; the zirconium alloy surface is polished and cleaned with abrasive paper, and surface dirt and oxide skin are removed; the zirconium alloy matrix is clamped and fixed to a laser cladding workbench, and the workbench is communicated with cooling water; and a laser cladding machine is used for cladding the Mo metal coating and the Hastelloy C2000 coating on the surface of the zirconium alloy matrix in sequence. The prepared composite coating is good in compactness and free of defects such as air holes and cracks, the composite coating is combined with a zirconium alloy matrix in a metallurgical mode, the composite coating is well combined with the zirconium alloy matrix under the 5% strain condition, and the cracking phenomenon is avoided. And the composite coating and the matrix have high bonding strength and synergistic deformation capacity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of laser cladding surface modification, and in particular to a high-bonding-strength composite coating on the surface of a nuclear zirconium alloy and a preparation method thereof. Background Art

[0002] Zirconium alloys have long been used in nuclear fuel reactor equipment for their low thermal neutron absorption cross section, high temperature oxidation resistance, excellent corrosion resistance and mechanical properties. However, in the Fukushima nuclear power plant accident, due to the loss of cooling water accident (LOCA), the zirconium alloy cladding of the nuclear fuel elements failed due to oxidation in a high temperature environment, producing a large amount of hydrogen, which caused the reactor device to explode and release a large amount of radioactive hazardous substances. In order to improve the safety and reliability of nuclear fuel cladding under loss of cooling water accident (LOCA) and beyond design basis accident (BDBA) conditions, the concept of accident tolerant fuel (ATF) was proposed. One of the core concepts of ATF research and development is to coat the surface of the zirconium alloy cladding with a protective coating based on the original fuel element and reactor structure design, and is committed to improving the accident tolerance of the zirconium alloy cladding under accident conditions and avoiding core melt accidents.

[0003] Coating the zirconium alloy cladding surface can not only improve the cladding's resistance to high-temperature steam oxidation under accident conditions, but also improve the cladding's corrosion resistance under normal operating conditions, thereby extending the service life of nuclear fuel elements. The coatings that have been studied so far include metal materials, ceramic materials, and multilayer structure coatings. The bonding strength between the substrate and the coating and the long-term protection of the coating under simulated conditions are key issues in the development of new coatings.

[0004] Based on the properties of zirconium alloys and the research results of coating preparation using existing processes, the metal Cr coating, which is currently being studied more, has limitations in its application performance under high temperature conditions. Under simulated accident conditions, Cr-Zr diffusion is prone to occur between the Cr coating and the zirconium alloy, resulting in dissolution and failure of the coating. Under high-temperature oxidation conditions, the Cr coating develops bulges and cracks and falls off the zirconium alloy, and therefore cannot provide long-term protection for the cladding. Summary of the invention

[0005] In order to solve the problem of bonding strength between the coating and the zirconium alloy cladding, the present invention adopts laser cladding technology to prepare a Mo intermediate layer between the coating and the substrate zirconium alloy to obtain a double-layer coating structure. The bonding method between the coating and the substrate is metallurgical bonding, which improves the bonding strength between the coating and the zirconium alloy, thereby improving the long-term effectiveness of the coating's resistance to high-temperature oxidation and corrosion resistance.

[0006] In order to achieve the above object, the specific technical solution adopted by the present invention is as follows:

[0007] In a first aspect, the present invention provides a high bonding strength composite coating on the surface of a nuclear zirconium alloy, which comprises a Mo coating and a Hastelloy C2000 coating from the inside to the outside.

[0008] Preferably, the Mo coating has a thickness of 200-300 μm.

[0009] Preferably, the thickness of the Hastelloy C2000 coating is 300-450 μm.

[0010] Preferably, the composition of Hastelloy C2000 is: Cr: 23%, Mo: 16%, Cu: 2.3%, Fe: 1.5%, and Ni: balance.

[0011] In the second aspect, the present invention provides a method for preparing a high bonding strength composite coating on the surface of the above-mentioned nuclear zirconium alloy. Currently, the main technologies for preparing zirconium alloy surface coatings include physical vapor deposition, spraying, and laser cladding. The present invention adopts laser cladding technology, and the prepared coating is combined with the substrate in a metallurgical bonding manner. Compared with other methods, the bonding force between the substrate and the coating is stronger. The laser cladding coating has a high solidification rate and can effectively refine the structure and improve the comprehensive performance of the coating.

[0012] The method for preparing the high bonding strength composite coating on the surface of the nuclear zirconium alloy specifically comprises the following steps:

[0013] (1) placing the metal powder in a drying furnace for drying;

[0014] (2) Grinding and cleaning the surface of the zirconium alloy plate with SiC water-abrasive sandpaper to remove surface dirt and oxide scale;

[0015] (3) The zirconium alloy substrate is clamped and fixed on a laser cladding workbench, and the workbench is connected to cooling water;

[0016] (4) using a laser cladding machine to clad a layer of Mo metal coating on the surface of the zirconium alloy substrate;

[0017] (5) A layer of Hastelloy C2000 coating is clad on the Mo metal coating using a laser cladding machine.

[0018] Preferably, in step (1), the particle size of the metal powder is 53-105 μm, the metal powder is dried for more than 4 hours, and the drying temperature is 80-120°C.

[0019] Preferably, in step (2), the surface of the zirconium alloy substrate is polished with 400-mesh SiC water-abrasive paper, and the zirconium alloy substrate is ultrasonically cleaned in alcohol for 10-15 minutes. The zirconium alloy grade used is Zr-4.

[0020] Preferably, the workbench for clamping the substrate in step (3) is copper, the surface is polished with 180-mesh SiC water-abrasive sandpaper, and the cooling water temperature is 20-26° C. The cooling operation can improve the bonding quality between the coating and the substrate.

[0021] Preferably, in step (4), the laser power is 400-1000 W, the laser scanning speed is 500-1200 mm / min, the powder feeding speed is 0.1-1 r / min, the overlap rate is 40-60%, and the protective gas flow rate is 15-20 L / min.

[0022] Preferably, in step (5), the laser power is 300-900 W, the laser scanning speed is 400-1000 mm / min, the powder feeding speed is 0.1-1 r / min, the overlap rate is 40-70%, and the protective gas flow rate is 15-20 L / min. The laser power and speed have a significant effect on the bonding quality between the coating and the substrate.

[0023] The present invention has the following beneficial effects:

[0024] 1. The double-layer coating structure designed by the invention uses metal Mo as the middle layer, which blocks the mutual diffusion of elements between the coating and the zirconium alloy at high temperature, avoids the generation of many brittle intermediate phases ZrM (Cr / Ni), and thus improves the bonding strength between the coating and the substrate. The double-layer coating prepared by laser cladding has a dense structure without pores. When the double-layer coating and the substrate are stretched to a strain of 5%, the coating and the substrate are still well combined, and no cracks are generated on the surface and inside of the coating.

[0025] 2. The present invention adopts laser cladding process to prepare zirconium alloy surface coating. The bonding method between the coating and the substrate is metallurgical bonding. Compared with other methods, the coating prepared by laser cladding has more advantages in bonding strength. Combined with the Mo / Hastelloy C2000 double-layer structure design, the coating can also provide long-term protection for the cladding under high-temperature oxidation conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a macroscopic surface image of a double-layer coating in an embodiment of the present invention;

[0027] Figure 2 This is a scanning electron microscope image of the cross section of the double-layer coating and the zirconium alloy substrate in an embodiment of the present invention;

[0028] Figure 3 This is an optical microscope image of a cross section of a double-layer coating and a zirconium alloy substrate stretched to 5% strain in an embodiment of the present invention;

[0029] Figure 4 This is an optical microscope image of the macroscopic surface of the double-layer coating and the zirconium alloy substrate under the condition of being stretched to 5% strain in an embodiment of the present invention;

[0030] Figure 5 This is an optical microscope image of a cross section of a Hastelloy C2000 single-layer coating and a zirconium alloy substrate stretched to 5% strain in Comparative Example 1 of the present invention;

[0031] Figure 6 This is a macroscopic surface image of a double-layer coating in Comparative Example 2 of the present invention which adopts a preparation process different from that in the embodiment. DETAILED DESCRIPTION

[0032] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments. The schematic implementation modes of the present invention and their description are only used to explain the present invention and are not intended to limit the present invention.

[0033] Example 1

[0034] In this embodiment, the Mo / Hastelloy C2000 double-layer coating is clad on the surface of the zirconium alloy substrate using the following preparation method, and the specific operation steps are as follows:

[0035] (1) Pretreatment of metal powder for laser cladding: Mo metal powder and Hastelloy C2000 metal powder are placed in a drying furnace for 4 hours at a drying temperature of 80-120°C, and the powder particle size is 53-105 μm;

[0036] (2) Surface pretreatment of the zirconium alloy substrate: The surface of the zirconium alloy was polished with 400-mesh SiC water-abrasive sandpaper, and the zirconium alloy substrate was ultrasonically cleaned in anhydrous ethanol for 15 minutes to remove dirt and oxide scale on the surface of the zirconium alloy substrate. The grade of the zirconium alloy was Zr-4.

[0037] (3) Clamping the zirconium alloy substrate: The zirconium alloy substrate is clamped and fixed on the laser cladding workbench. The workbench material is copper. The copper surface is polished with 180 mesh SiC water-abrasive sandpaper with a thickness of 20 mm. The workbench is connected to cooling water at a temperature of 25 °C.

[0038] (4) Laser cladding Mo coating: A layer of Mo metal coating is clad on the surface of the zirconium alloy substrate using a laser cladding machine. The laser power is 500 W, the laser scanning speed is 800 mm / min, the powder feeding speed is 0.2 r / min, the overlap rate is 58%, and the shielding gas flow rate is 18 L / min.

[0039] (5) Laser cladding of Hastelloy C2000 coating: A layer of Hastelloy C2000 coating was clad on the surface of the Mo coating using a laser cladding machine. The laser power was 430 W, the laser scanning speed was 520 mm / min, the powder feeding speed was 0.3 r / min, the overlap rate was 42%, and the shielding gas flow rate was 18 L / min.

[0040] Example 2

[0041] In this embodiment, the Mo / Hastelloy C2000 double-layer coating is clad on the surface of the zirconium alloy substrate using the following preparation method, and the specific operation steps are as follows:

[0042] (1) Pretreatment of metal powder for laser cladding: Mo metal powder and Hastelloy C2000 metal powder are placed in a drying furnace for 4 hours at a drying temperature of 80-120°C, and the powder particle size is 53-105 μm;

[0043] (2) Surface pretreatment of the zirconium alloy substrate: The surface of the zirconium alloy was polished with 400-mesh SiC water-abrasive sandpaper, and the zirconium alloy substrate was ultrasonically cleaned in anhydrous ethanol for 15 minutes to remove dirt and oxide scale on the surface of the zirconium alloy substrate. The grade of the zirconium alloy was Zr-4.

[0044] (3) Clamping the zirconium alloy substrate: The zirconium alloy substrate is clamped and fixed on the laser cladding workbench. The workbench material is copper. The copper surface is polished with 180 mesh SiC water-abrasive sandpaper with a thickness of 20 mm. The workbench is connected to cooling water at a temperature of 25 °C.

[0045] (4) Laser cladding Mo coating: A layer of Mo metal coating is clad on the surface of the zirconium alloy substrate using a laser cladding machine. The laser power is 500 W, the laser scanning speed is 600 mm / min, the powder feeding speed is 0.2 r / min, the overlap rate is 58%, and the shielding gas flow rate is 18 L / min.

[0046] (5) Laser cladding of Hastelloy C2000 coating: A layer of Hastelloy C2000 coating was clad on the surface of the Mo coating using a laser cladding machine. The laser power was 450 W, the laser scanning speed was 500 mm / min, the powder feeding speed was 0.3 r / min, the overlap rate was 50%, and the shielding gas flow rate was 18 L / min.

[0047] Example 3

[0048] In this embodiment, the Mo / Hastelloy C2000 double-layer coating is clad on the surface of the zirconium alloy substrate using the following preparation method, and the specific operation steps are as follows:

[0049] (1) Pretreatment of metal powder for laser cladding: Mo metal powder and Hastelloy C2000 metal powder are placed in a drying furnace for 4 hours at a drying temperature of 80-120°C, and the powder particle size is 53-105 μm;

[0050] (2) Surface pretreatment of the zirconium alloy substrate: The surface of the zirconium alloy was polished with 400-mesh SiC water-abrasive sandpaper, and the zirconium alloy substrate was ultrasonically cleaned in anhydrous ethanol for 15 minutes to remove dirt and oxide scale on the surface of the zirconium alloy substrate. The grade of the zirconium alloy was Zr-4.

[0051] (3) Clamping the zirconium alloy substrate: The zirconium alloy substrate is clamped and fixed on the laser cladding workbench. The workbench material is copper. The copper surface is polished with 180 mesh SiC water-abrasive sandpaper with a thickness of 20 mm. The workbench is connected to cooling water at a temperature of 25 °C.

[0052] (4) Laser cladding Mo coating: A layer of Mo metal coating is clad on the surface of the zirconium alloy substrate using a laser cladding machine. The laser power is 600 W, the laser scanning speed is 1000 mm / min, the powder feeding speed is 0.1 r / min, the overlap rate is 58%, and the shielding gas flow rate is 18 L / min.

[0053] (5) Laser cladding of Hastelloy C2000 coating: A layer of Hastelloy C2000 coating was clad on the surface of the Mo coating using a laser cladding machine. The laser power was 420 W, the laser scanning speed was 500 mm / min, the powder feeding speed was 0.3 r / min, the overlap rate was 42%, and the shielding gas flow rate was 18 L / min.

[0054] Comparative Example 1

[0055] Compared with the embodiment, this comparative example is different in coating structure design. A single layer of Hastelloy C2000 coating is clad on the surface of a zirconium alloy substrate using the following preparation method. The specific operation steps are as follows:

[0056] (1) Pretreatment of metal powder for laser cladding: Place Hastelloy C2000 metal powder in a drying furnace for 4 hours at a drying temperature of 80-120°C, and the powder particle size is 53-105 μm;

[0057] (2) Surface pretreatment of the zirconium alloy substrate: The surface of the zirconium alloy was polished with 400-mesh SiC water-abrasive sandpaper, and the zirconium alloy substrate was ultrasonically cleaned in anhydrous ethanol for 15 minutes to remove dirt and oxide scale on the surface of the zirconium alloy substrate. The grade of the zirconium alloy was Zr-4.

[0058] (3) Clamping the zirconium alloy substrate: The zirconium alloy substrate is clamped and fixed on the laser cladding workbench. The workbench material is copper. The copper surface is polished with 180 mesh SiC water-abrasive sandpaper with a thickness of 20 mm. The workbench is connected to cooling water at a temperature of 25 °C.

[0059] (4) Laser cladding of Hastelloy C2000 coating: A layer of Hastelloy C2000 coating was clad on the surface of the zirconium alloy substrate using a laser cladding machine. The laser power was 420 W, the laser scanning speed was 510 mm / min, the powder feeding speed was 0.4 r / min, the overlap rate was 50%, and the shielding gas flow rate was 16 L / min.

[0060] Comparative Example 2

[0061] Compared with the embodiment, the preparation process of this comparative example is different. The following preparation method is used to clad the Mo / Hastelloy C2000 double-layer coating on the surface of the zirconium alloy substrate. The specific operation steps are as follows:

[0062] (1) Pretreatment of metal powder for laser cladding: Mo metal powder and Hastelloy C2000 metal powder are placed in a drying furnace for 4 hours at a drying temperature of 80-120°C, and the powder particle size is 53-105 μm;

[0063] (2) Surface pretreatment of the zirconium alloy substrate: The surface of the zirconium alloy was polished with 400-mesh SiC water-abrasive sandpaper, and the zirconium alloy substrate was ultrasonically cleaned in anhydrous ethanol for 15 minutes to remove dirt and oxide scale on the surface of the zirconium alloy substrate. The grade of the zirconium alloy was Zr-4.

[0064] (3) Clamping the zirconium alloy substrate: The zirconium alloy substrate is clamped and fixed on the laser cladding workbench. The workbench material is copper. The copper surface is polished with 180 mesh SiC water-abrasive sandpaper with a thickness of 20 mm.

[0065] (4) Laser cladding Mo coating: A layer of Mo metal coating is clad on the surface of the zirconium alloy substrate using a laser cladding machine. The laser power is 600 W, the laser scanning speed is 1000 mm / min, the powder feeding speed is 0.1 r / min, the overlap rate is 58%, and the shielding gas flow rate is 18 L / min.

[0066] (5) Laser cladding of Hastelloy C2000 coating: A layer of Hastelloy C2000 coating was clad on the surface of the Mo coating using a laser cladding machine. The laser power was 1000 W, the laser scanning speed was 1200 mm / min, the powder feeding speed was 0.3 r / min, the overlap rate was 50%, and the shielding gas flow rate was 18 L / min.

[0067] The morphology of the double-layer coating obtained in Examples 1-3 is as follows: Figure 1-2 As shown, it can be seen that the composite coating has good density and no defects such as pores and cracks. The samples of Examples 1-3 and Comparative Example 1 were cut into tensile specimens and stretched to 5% strain. The bonding between the coating and the substrate is shown in Figure 3-5 As shown in Table 1 below, after the samples of Examples 1-3 were stretched, the coating and the substrate were tightly bonded, and no cracks were generated on the macroscopic surface of the coating. Compared with the examples, in Comparative Example 1, Mo was not used as an intermediate layer, and only a single layer of Hastelloy C2000 was used. After the sample was stretched to a strain of 5%, the coating peeled off from the substrate surface. Compared with the examples, the preparation process of the double-layer structure coating prepared in Comparative Example 2 was different. Specifically, the substrate was not cooled during the preparation of the Hastelloy C2000 layer, and the laser power and laser scanning speed were beyond the parameter range in the examples. As a result, cracks were generated on the coating surface, and the coating and the substrate were obviously peeled off.

[0068] From the above data analysis, it can be seen that the double-layer coating prepared under the process parameters of the present invention has good bonding performance with the zirconium alloy substrate, the coating is dense, has no defects such as pores and cracks, and has good strength and toughness.

[0069] Table 1 Test results of cladding coating samples on zirconium alloy substrate

[0070]

[0071] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A high bonding strength composite coating on the surface of a nuclear zirconium alloy, characterized in that: From inside to outside, they are Mo coating and Hastelloy C2000 coating respectively.

2. The high bonding strength composite coating on the surface of nuclear zirconium alloy according to claim 1, characterized in that: The thickness of the Mo coating is 200-300 μm.

3. The high bonding strength composite coating on the surface of nuclear zirconium alloy according to claim 1, characterized in that: The thickness of the Hastelloy C2000 coating is 300-400 μm.

4. The high bonding strength composite coating on the surface of nuclear zirconium alloy according to claim 1, characterized in that: The composition of Hastelloy C2000 is: Cr: 23%, Mo: 16%, Cu: 2.3%, Fe: 1.5%, Ni: balance.

5. The method for preparing a high bonding strength composite coating on the surface of a nuclear zirconium alloy according to any one of claims 1 to 4, characterized in that: The following steps are involved: (1) placing the metal powder in a drying furnace for drying; (2) Grinding and cleaning the surface of the zirconium alloy plate with SiC water-abrasive sandpaper to remove surface dirt and oxide scale; (3) The zirconium alloy substrate is clamped and fixed on a laser cladding workbench, and the workbench is connected to cooling water; (4) using a laser cladding machine to clad a layer of Mo metal coating on the surface of the zirconium alloy substrate; (5) A layer of Hastelloy C2000 coating is clad on the Mo metal coating using a laser cladding machine.

6. The method for preparing a high bonding strength composite coating on the surface of a nuclear zirconium alloy according to claim 5, characterized in that: In step (1), the particle size of the metal powder is 53-105 μm, the metal powder is dried for more than 4 hours, and the drying temperature is 80-120° C.

7. The method for preparing a high bonding strength composite coating on the surface of a nuclear zirconium alloy according to claim 5, characterized in that: In step (2), the surface of the zirconium alloy substrate is polished with 400-mesh SiC water-abrasive paper, and the zirconium alloy substrate is ultrasonically cleaned in alcohol for 10-15 minutes. The zirconium alloy grade used is Zr-4.

8. The method for preparing a high bonding strength composite coating on the surface of a nuclear zirconium alloy according to claim 5, characterized in that: In step (3), the workbench for holding the substrate is made of copper, the surface of which is polished with 180-mesh SiC water-abrasive sandpaper, and the cooling water temperature is 20-26°C.

9. The method for preparing a high bonding strength composite coating on the surface of a nuclear zirconium alloy according to claim 5, characterized in that: In step (4), the laser power is 400-1000W, the laser scanning speed is 500-1200mm / min, the powder feeding speed is 0.1-1r / min, the overlap rate is 40-60%, and the protective gas flow rate is 15-20L / min.

10. The method for preparing a high bonding strength composite coating on the surface of a nuclear zirconium alloy according to claim 5, characterized in that: In step (5), the laser power is 300-900 W, the laser scanning speed is 400-1000 mm / min, the powder feeding speed is 0.1-1 r / min, the overlap rate is 40-70%, and the protective gas flow rate is 15-20 L / min.